Introduktion: Resultatstyring dengang og i dag: Version 2.0, 3.0, 4.0? - Brødsgaard, Marie-Louise Frølich; Gjørling, Mathias; Grøn, Caroline Howard; Kristiansen, Mads Bøge (Politik, 2015)
Introduktion